2017
DOI: 10.1111/hel.12392
|View full text |Cite
|
Sign up to set email alerts
|

Optimization strategies aimed to increase the efficacy of H. pylori eradication therapies

Abstract: Using potent acid inhibition and/or higher antibiotic doses-especially by increasing the number of daily intakes-and lengthening treatments up to 14 days improves efficacy in most regimens and should be generally recommended. Triple therapies can be efficiently improved by the addition of bismuth salts, turning them into quadruple therapies. Finally, some treatments will require a combination of optimization strategies to significantly improve results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 124 publications
(254 reference statements)
2
79
0
23
Order By: Relevance
“…This study shows that high‐dose metronidazole in a PPI, clarithromycin, and metronidazole combination was unable to achieve high cure rates, and we suggest that this therapy should not be used in areas where dual resistance is a problem. However, bismuth is one of the few antimicrobials to which resistance has not developed and provides an additive effect which has been reported to improve cure rates significantly . Although the percent of improvement was limited by the relative high cure rates, overall in this study, the addition of bismuth appeared to increase the cure rate by ~26% (PP) and 21.2% (ITT).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This study shows that high‐dose metronidazole in a PPI, clarithromycin, and metronidazole combination was unable to achieve high cure rates, and we suggest that this therapy should not be used in areas where dual resistance is a problem. However, bismuth is one of the few antimicrobials to which resistance has not developed and provides an additive effect which has been reported to improve cure rates significantly . Although the percent of improvement was limited by the relative high cure rates, overall in this study, the addition of bismuth appeared to increase the cure rate by ~26% (PP) and 21.2% (ITT).…”
Section: Discussionmentioning
confidence: 57%
“…Although the percent of improvement was limited by the relative high cure rates, overall in this study, the addition of bismuth appeared to increase the cure rate by ~26% (PP) and 21.2% (ITT). Our previous study showed that bismuth improved the outcome with standard‐dose metronidazole suggesting that the effect may not always require high‐dose metronidazole . These results suggest that the addition of bismuth is a rational strategy for therapies where resistance has reduced the effectiveness of currently available therapies.…”
Section: Discussionmentioning
confidence: 87%
“…This is copper‐fastened by a new systematic review of all optimisation strategies for H. pylori eradication that shows the most direct way to optimize a treatment is using higher doses of drugs unless it has been shown that lower doses are equally effective. This applies to the use of potent acid inhibition and/or higher antibiotic doses‐especially by increasing the number of daily intakes‐and lengthening treatments up to 14 days . Bismuth based therapies are performing very well across numerous regions and the more novel pairings of it either as part of a “single triple” capsule or with other antibiotics may well enable clinicians to overcome some of the issues around tetracycline supply that have hampered the widespread adoption of bismuth based therapy.…”
Section: Resultsmentioning
confidence: 99%
“…There have been many and varied number of studies pertaining to treatments up to 14 days. 112 Bismuth based therapies are performing very well across numerous regions and the more novel pairings of it either as part of a "single triple" capsule or with other antibiotics may well enable clinicians to overcome some of the issues around tetracycline supply that have hampered the widespread adoption of bismuth based therapy. Levofloxacin and rifabutin remain useful alternatives, especially in rescue therapy settings.…”
Section: Discussionmentioning
confidence: 99%
“…When reviewing recent publications, as well as the “golden rules of therapy optimisation in H. pylori ”, it is easy to conclude that there is room for improvement in the regimens used at our centre: (a) an ITT effectiveness of 90% was achieved in a study using RIF 150 mg q.d. combined with AMO ≥1 g t.i.d and pantoprazole 80 mg t.i.d.…”
Section: Discussionmentioning
confidence: 99%